Feline Sporotrichosis in the periocular region - Successful Treatment with Itraconazole - Marques, Ana Beatriz da Silva; Smaniotto, Crisan; Dias, Deborah Caroline Sepúlveda; Gusso, Ana Bianca Ferreira; Carvalho, Raquel Jordana de Mello Pires de; Camargo, Mauro Henrique Bueno de; Marcusso, Paulo Fernandes; Merlini, Natalie Bertelis (Acta Scientiae Veterinariae, 2022)
Background: Sporotrichosis is a zoonotic disease caused by a dimorphic fungi of the Sporothrix schenckii complex. It is an emerging zoonosis with worldwide distribution, thus of great importance to public health. The infection occurs from traumatic inoculation of the fungus in the human skin from contaminated plants and soils and through bites or scratches of infected animals. The occurrence of sporotrichosis has been related to zoonotic transmission, especially by domestic felines. This work aims to report the successful use of itraconazole as monotherapy in a case of localized feline sporotrichosis and highlight the effectiveness of cytology in its diagnosis. Case: A 1-year-and-4-month-old spayed female cat undefined breed, weighing 3.1 kg, was referred to the Veterinary Medical Teaching Hospital of the Universidade Estadual de Maringá (UEM), city of Umuarama, presenting a serosanguinous ulcerative lesion located in the left periocular region The clinical picture of the patient progressed over 3 months. Treatments with antibiotic therapy, corticosteroids, and surgical procedures were conducted, without clinical improvement. A new lesion in the distal portion of the thoracic limb emerged, proving that the disease remained in progression. Hematological exams were performed, among them hemogram, renal and hepatic biochemical analyses, SNAPS to identify the feline immunodeficiency virus feline leukemia virus (FIV/FeLV), and cytology of the lesion through imprints. The hematological results were all within the normal standards for the species. Cytology showed a large amount of oval and fusiform structures phagocyted by polymorphonuclear cells, free at the bottom of the slide, compatible with Sporothrix spp. The treatment administered was itraconazole (100 mg/cat), orally administered every 24 h, cefovecin sodium 8 mg/kg, subcutaneous, single dose, topical use of antifungal ointment based on ketoconazole, twice a day. The animal underwent periodic physical and hematological evaluations throughout the treatment period, without significant changes. Complete remission of the lesion was observed after 25 weeks of treatment. Discussion: Cutaneous lesions caused by Sporothrix spp. are mainly located in the head, specifically in the nasal plane, pinna, and periocular regions, presenting ulcerative characteristics and exudate. The dissemination of the fungus through the animal’s body may occur through autoinoculation while the feline scratches or licks itself. The cytology presents high sensitivity for diagnosing feline sporotrichosis due to the high fungal load found in the cutaneous lesions. In addition, it is a technique easy to perfom and presents immediate results, favoring an early beginning of the therapy. Itraconazole is considered the drug of choice for the treatment of sporotrichosis because of its efficacy and safety compared to that of other antifungal drugs. The average time of treatment is 4 to 9 months in cats, and it must be maintained for another month after complete remission of the clinical signs to prevent the reactivation of the lesions. FIV and FeLV are not predominant factors for the development of the disease. The use of itraconazole as monotherapy proved to be effective, with no side effects throughout the treatment. Cytology was satisfactory as a diagnostic method and allowed immediate initiation of therapy. Awareness regarding the forms of transmission and prevention of this zoonosis is instrumental. Keywords: Sporothrix spp., zoonosis, monotherapy, itraconazole, cytology. Título: Esporotricose felina na região periocular - eficácia do tratamento com itraconazol. Descritores: Sporothrix spp., zoonose, monoterapia, itraconazol, citologia.